Limited effects of oral drench of mineral supplement for treating Mycoplasma bovis in mixed-sex bison (Bison bison) yearlings - Martin, Jeff M.; Kruse, Carter G.; Bragg, Tom K.; Urso, Philip M. (Frontiers in Conservation Science, 2026)
Trace minerals found in the diet are essential for animal health, but the role of mineral supplementation in maintaining bison health or boosting immune response is relatively unknown. This study evaluated the impact of an oral drench supplement containing Co, Cu, Se, and Zn—minerals associated with immune function—in reducing mortality and maintaining health in response to a Mycoplasma bovis outbreak in yearling bison. A total of 1,295 mixed-sex, non-reproductive yearlings were studied, with 464 receiving the supplement and 831 serving as controls. Mortality totaled 238 individuals (18.4%), with no statistically significant difference between groups (Pearson’s χ² test, p>0.05), indicating supplement ineffectiveness. Blood analysis confirmed no change in mineral status, suggesting that the supplement formulation, intended for cattle, may not meet bison-specific requirements. Water quality analysis of water sources used in the study revealed elevated Fe and manganese levels, but other mineral imbalances were not evident. Growth rates and final weights did not differ significantly between treatment and control groups, although males consistently outweighed females. Parasitological analyses showed minor differences in gastrointestinal nematode burdens, with no apparent link to supplementation or mortality. Serology results indicated significant differences but were likely of limited biological relevance. Finally, the study highlighted the potential implications of frequent bison handling for research or other purposes, which may increase stress and disease susceptibility. These findings underscore the need for bison-specific mineral information, as well as diagnostic, prevention, and treatment strategies to improve health management in this species.